In vitro and in vivo assessment of decellularized platelet-rich fibrin-loaded strontium doped porous magnesium phosphate scaffolds in bone regeneration. (February 2023) - Tarif, Chaudhuri Mohammad; Mandal, Santanu; Chakraborty, Bijayashree; Sarkar, Kaushik; Mukherjee, Prasenjit; Roy, Mangal; Nandi, Samit Kumar
Abstract: The present work reports the effect of decellularized platelet-rich fibrin (dPRF) loaded strontium (Sr) doped porous magnesium phosphate (MgP) bioceramics on biocompatibility, biodegradability, and bone regeneration. Sustained release of growth factors from dPRF is a major objective here, which conformed to the availability of dPRF on the scaffold surface even after 7 days of in vitro degradation. dPRF-incorporated MgP scaffolds were implanted in the rabbit femoral bone defect and bone rejuvenation was confirmed by radiological examination, histological examination, fluorochrome labeling study, and micro-CT. μ-CT examination of the regained bone samples exhibited that invasion of mature bone in the pores of the MgP2Sr-dPRF sample was higher than the MgP2Sr which indicated better bone maturation capability of this composition. Quantifiable assessment using oxytetracycline labeling showed 73.55 ± 1.12% new osseous tissue regeneration for MgP2Sr-dPRF samples in contrast to 65.47 ± 1.16% for pure MgP2Sr samples, after 3 months of implantation. Histological analysis depicted the presence of abundant osteoblastic and osteoclastic cells in dPRF-loaded Sr-doped MgP samples as compared to other samples. Radiological studies also mimicked similar results in the MgP2Sr-dPRF group with intact periosteal lining and significant bridging callus formation. The present results indicated that dPRF-loaded Sr-doped magnesium phosphate bioceramics have good biocompatibility, bone-forming ability, and suitable biodegradability in bone regeneration. Graphical abstract: Image 1 Highlights: Decellularized plasma-rich fibrin-loaded magnesium phosphate ceramics enhances bone defect healing. The decellularized plasma-rich fibrin was successfully loaded within the pores of magnesium phosphate ceramics . Excellent bone regeneration was achieved while the gradual degradation of magnesium phosphate ceramics.